204 Growth Factor Concentration Can Vary in Platelet-Rich Plasma from Men with Erectile Dysfunction. Issue 1 (1st April 2022) - Khodamoradi, K; Dullea, A; Golan, R; Molina Leyba, M; Masterson, T; Arora, H; Ramasamy, R
ABSTRACT: Introduction: Erectile Dysfunction (ED) affects 40% of men over 40 and every decade after increases the likelihood by 10% (1). Platelet Rich Plasma (PRP) is a restorative therapy rich in cytokines and growth factors that may reverse the underlying pathology of ED (2). Before PRP can be used effectively in clinic, it is necessary to understand if its components are similar among men with ED. Objective: To determine whether growth factors vary among PRP of men with ED Methods: Blood was obtained from three men with ED and one healthy man as a control. The Arthrex Angel system was used to extract their PRP. The sample was immediately stored in ice and kept in -80 C. Bradford assay was ran to ensure equal protein concentrations were used. The Abcam Human Growth Factor Antibody Array kit (ab134002) was used to simultaneously detect 41 human growth factors. Results: Subject 1 was 43 years old with ED only. Subject 2 was 43 years old with obstructive sleep apnea, hyperlipidemia, and delayed sleep phase syndrome, and BMI 27.1. Subject 3 was 49 years old with hypertension, diabetes mellitus (not on insulin), asthma, high cholesterol, and BMI 32.4.The results of evaluating the 41 growth factor array showed that several growth factors had a fold change greater than 1.5 compared to the control. In PRP of adults with ED, PDGF-AA, PDGF- AB, and PDGF-AB had a greater than 1.5-fold change in at least 2 out of the 3 samples when compared to control. In FGF-6, GM-CSF, NT-3, TGF-α, TGF-β, and TGF-β2, there was a negative fold change of greater than 1.5 in at least 2 out of the 3 samples when compared to control. Conclusions: Based on these results, the use of PRP as a therapeutic agent may need to be personalized based on individuals' age, comorbidities, or growth factor content. Individuals with underlying comorbidities may need different volumes of PRP. Our future ongoing research is focusing on particular growth factors within PRP that are responsible for improvement in erectile function, thus being able to personalize PRP therapy for me with ED. Citations: 1. Feldman HA, Goldstein I, Hatzichristou DG, Krane RJ, McKinlay JB. Impotence and its medical and psychosocial correlates: results of the Massachusetts Male Aging Study. J Urol. 1994;151(1):54-61. 2. Liu MC, Chang ML, Wang YC, Chen WH, Wu CC, Yeh SD. Revisiting the Regenerative Therapeutic Advances Towards Erectile Dysfunction. Cells. 2020;9(5). 3. Fang J, Huang X, Han X, Zheng Z, Hu C, Chen T, et al. Endothelial progenitor cells promote viability and nerve regenerative ability of mesenchymal stem cells through PDGF-BB/PDGFR-beta signaling. Aging (Albany NY). 2020;12(1):106-21. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Acerus Pharmaceutical